Advances in chitosan-based nanoparticles for oncotherapy. (15th October 2019) - Zhang, Enhui; Xing, Ronge; Liu, Song; Qin, Yukun; Li, Kecheng; Li, Pengcheng
Highlights: Latest progress on chitosan-based nanoparticles for oncotherapy is summarized. The factors that affect the efficacy of chitosan-based nanoparticles are listed. The challenges and further development are discussed. Abstract: Chitosan has attracted considerable attention as an anti-tumor drug carrier material in recent years, which is due to its biocompatibility and biodegradability, as well as the simple and mild preparing techniques of drug-loaded nanoparticles. Chitosan-based nanoparticles can deliver various anti-tumor agents to specific tumor tissues by passive and active targeting mechanisms, including traditional chemotherapeutic agents, DNA or siRNA, proteins, photosensitizers and so on. In this review, we summarized the factors affecting the anti-tumor efficacy of chitosan-based nanoparticles, to aid exploring the function-structure relationship. The recent studies on chitosan-based nanoparticles for oncotherapy were highlighted, including their structures, properties and pharmacological effects. Finally, we offered our perspectives on the challenges and future development of this area.